2015
DOI: 10.1016/j.drugalcdep.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cigarette smoking and cannabis dependence: A longitudinal study of young cannabis users in the United Kingdom

Abstract: HighlightsWe studied the extent that cigarette smoking predicts level of cannabis addiction.We tested whether cigarette smoking mediates the effect of cannabis use on dependence.We interviewed 298 cannabis and tobacco users, of which 65 were followed up.Cigarette smoking accounted for 29% of the variance in cannabis dependence.Cigarette smoking mediated the relationship between cannabis use and dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
57
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 48 publications
13
57
1
2
Order By: Relevance
“…The comparatively rarer outcomes of tobacco dependence, other drug use and other drug dependence were found to be associated with increased speed of progression to cannabis dependence. The use of both tobacco and cannabis has been frequently observed (Agrawal et al, 2012, 2010; Hindocha et al, 2015), and regular cigarette smokers are more likely to report earlier cannabis use opportunity (Agrawal et al, 2013). Present results strongly supported this finding, and extend it to show weekly tobacco use and dependence were significantly associated with speed of progression to cannabis dependence.…”
Section: Discussionmentioning
confidence: 99%
“…The comparatively rarer outcomes of tobacco dependence, other drug use and other drug dependence were found to be associated with increased speed of progression to cannabis dependence. The use of both tobacco and cannabis has been frequently observed (Agrawal et al, 2012, 2010; Hindocha et al, 2015), and regular cigarette smokers are more likely to report earlier cannabis use opportunity (Agrawal et al, 2013). Present results strongly supported this finding, and extend it to show weekly tobacco use and dependence were significantly associated with speed of progression to cannabis dependence.…”
Section: Discussionmentioning
confidence: 99%
“…It is very common for cannabis users to present with other substance use problems, most notably those related to use of tobacco. In fact, most cannabis users also smoke tobacco (Badiani 2015), and smoking tobacco may potentiate cannabis dependence (Hindocha 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Cannabis use has been associated with an increased risk of nicotine dependence and greater nicotine dependence severity among co-users (Agrawal et al, 2008; Okoli et al, 2008). Tobacco use has been associated with increased risk of cannabis use and progression to the development of cannabis dependence (Agrawal et al, 2009) and has been shown to mediate the relationship between cannabis use and dependence (Hindocha et al, 2015). Third, co-users of tobacco and cannabis may have worse cessation outcomes.…”
Section: Introductionmentioning
confidence: 99%